Konstruksi Keilmuan Muhammadiyah dan NU - Sembodo Ardi Widodo (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
To understand Islamic body of knowledge in Indonesia is inseparable from the two biggest Islamic organizations, Muhammadiyah and Nahdlatul Ulama. Both organizations have their unique scientific structure; thus, in any case are different. On the one hand, there are similarities in resources, references, and teachers of the founder of both organizations. Yet, because of ideological factors in understanding Islam and also socio-cultural factors make the body of knowledge of Muhammadiyah and Nahdlatul Ulama so different. On the other hand, there have been distinguished aspects, if they are critically analyzed, that is, the difference on methodology, not on the primer resources.